International best practices in health care management - Buttigieg, Sandra C.; Rathert, Cheryl; Eiff, Wilfried von (Advances in health care management ;, 2015)
Significant variations in the quality of health care management practices are present both within and across local, regional, and international health systems. With increasing globalization of health services, both quality and efficiency of care can benefit from shared learning on a regional and global basis. Although systems and quality of health care delivery differ across the world, empirical research has found that people involved in health care, whether in the role of patients or health care providers, have similar wants and needs. Identifying and documenting best practices within and across countries is more important than ever. Best practices in health care management organize clinical and administrative processes in ways that achieve leapfrog results as compared to normal standards in industry, potentially earning brand status. Advances in health care management volume 17 helps to shape emerging thinking about best practices in international health care management. The volume is divided into two sections: a set of commentaries from US and European scholars, and research articles that compare two or more health systems and focus on specific topics in health care delivery.